- #26

Ray Vickson

Science Advisor

Homework Helper

Dearly Missed

- 10,706

- 1,728

You are having trouble here because either you only read the (last) half of what I wrote, or else have forgotten the first half when you read the second half. That is absolutely my last word on this topic.##Q_m = \sum_{i=1}^m \sum_{j=1}^m a_{ij} x_i x_j## and ##Q_k = \sum_{i=1}^k \sum_{j=1}^k a_{ij} x_i x_j##

I see this part.

Is the following true?

##Q_k = Q_m - \sum_{i=k+1}^m \sum_{j=k+1}^m a_{ij} x_i x_j##

If so, then since ##Q_m > 0##, how do we know this second term is not ##=> Q_m##?